2017
DOI: 10.1002/cncr.30559
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and the risk of cancer among elderly US adults: A registry‐based case‐control study

Abstract: Background: Hepatitis C virus (HCV) infection causes hepatocellular carcinoma (HCC) and subtypes of non-Hodgkin lymphoma (NHL). Associations with other cancers are not established. We systematically assessed associations between HCV infection and cancers in the US elderly population. Methods: We conducted a registry-based case-control study using the SEER-Medicare data in US adults aged ≥66 years. Cases (n=1,623,538) were people with first cancers identified in SEER registries (1993–2011). Controls (n=200,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 49 publications
5
120
0
3
Order By: Relevance
“…The inverse associations between HBV infection and cancers of the breast and prostate were similar to those observed for HCV infection . One possible explanation for this association was that HBV‐infected individuals may be less likely to get screened for cancer than HBV‐uninfected individuals.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The inverse associations between HBV infection and cancers of the breast and prostate were similar to those observed for HCV infection . One possible explanation for this association was that HBV‐infected individuals may be less likely to get screened for cancer than HBV‐uninfected individuals.…”
Section: Discussionsupporting
confidence: 54%
“…MDS is a heterogeneous group of malignancies characterized by ineffective ‐myeloid blood cell production with an increased risk of acute myeloid leukemia . HCV infection has been previously found to be associated with both DLBCL and MDS . Though we were likely to miss claims for HCV infection, confounding due to HCV infection is improbable because it is rare in the general population, and its associations with DLBCL and MDS were modest.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent registry-based case-control study 22 using the Surveillance, Epidemiology, and End Results (SEER)-Medicare database in U.S. adults aged ≥65 years from 1993 to 2011 found that as expected, HCV infection was strongly associated with cancers of the liver compared to those without HCV infection. Interestingly, however, HCV infection was also associated with higher odds of intrahepatic (adjusted odds ratio (aOR): 3.40) and extrahepatic (aOR: 1.90) bile duct cancer; pancreatic cancer (aOR: 1.23); anal cancer (aOR: 1.97); nonmelanoma nonepithelial skin cancer (aOR: 1.53); myelodysplastic syndrome (aOR: 1.56), and diffuse large B-cell lymphoma (aOR: 1.57).…”
Section: Hcv Infection and Extra-hepatic Clinical Outcomesmentioning
confidence: 71%
“…In patients with HCV-related cirrhosis, annual rate of HCC is 1%-4%, therefore patients with advanced fibrosis and cirrhosis should undergo HCC surveillance. The risk factors for HCC are older age, black race, HCV genotype 1b, co-infection with HBV or HIV, diabetes, obesity, steatosis, heavy alcohol consumption and low platelet levels in patients with cirrhosis [49][50][51][52] .…”
Section: Chronic Hepatitis Cmentioning
confidence: 99%